Difficulties Faced by Iraqi EFL learners in Using Past Tense - Diyar M. al-Musawi; Dumue Khalil Kareem (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Iraqi English as a Foreign Language (EFL) learners typically spend around eight years studying English before entering university. During the last four years of high school, students get frequent and rigorous instruction in English tenses. In addition, when they Upon entering the institution, students enroll in the English department where they engage in a rigorous four-year study of the English language. The curriculum is built with a focus on teaching tense. Grammar is taught for a total of three hours each week over a span of thirty weeks per year during these four years. However, Iraqi English as a Foreign Language (EFL) learners have significant difficulties in many grammatical aspects, particularly in the understanding and use of tenses. This article is a data analysis research that seeks to detect grammatical mistakes, including their nature, kinds, and origins. It is presumed in this context that you are now experiencing a difficulty, and I would want to know what specific issue you encountered in the past. The Past tense is used to describe previous activities that occurred either at a precise point in time, which may be indicated by a time phrase or inferred from the surrounding context. The past continuous tense is used to depict acts or occurrences that occurred at a period prior to the present moment.